Apolipoprotein E ε4: A Possible Risk Factor of Intracranial Pressure and White Matter Perfusion in Good-Grade Aneurysmal Subarachnoid Hemorrhage Patients at Early Stage - Peng, Jian-hua; Qin, Xing-hu; Pang, Jin-wei; Wu, Yue; Dong, Jin-hu; Huang, Chang-ren; Wan, Wei-feng; Yang, Xiao-bo; Sun, Xiao-chuan; Chen, Li-gang; Jiang, Yong (Frontiers in Neurology, 2017)
Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating and complicated disease with significant morbidity and mortality. Previous studies have shown that genetic susceptibility may play an important role in the outcome of a given individual with aSAH. This study evaluate the potential association in effects of the APOE allele on the early brain injury (EBI) in light of elevated intracranial pressure (ICP) and cerebral perfusion disorders in a consecutive series of noncomatose Chinese patients with aSAH. A total of 122 patients with aSAH (54 males and 68 females) were enrolled in this study. Demographic and clinical data were collected. We measured ICP before microsurgical clipping or endovascular coiling during the first 72 h after aneurysm rupture. Computed tomography perfusion (CTP) examination in patients was performed before treatment. The distributions of APOE genotypes and alleles matched Hardy-Weinberg law (p >0.05). In this study, 68 patients (55.7%) had a normal ICP, whereas 54 (44.3%) had an elevated ICP. Fourteen of 21 patients with APOE ε4 had an elevated ICP, which was significantly different from those without APOE ε4 (p =0.03). The patients with the ε4 allele had a higher incidence of elevated ICP (p =0.009, 95%, CI =1.481-15.432, OR =4.780) than those without this allele. For CTP measurements, a lower mean cerebral blood flow (CBF) (difference, -4.74; 95% CI, 0.53 to 8.94 s, p=0.03), longer mean transit time (MTT) (difference, 0.47; 95% CI, -0.87 to -0.78, p=0.02) and time-to-peak (TTP) (difference, 2.29; 95% CI, -3.64 to -0.93 s, p=0.02) were observed in patients with ε4 allele than in those without in the internal cupsule regions. In conclusion, the APOE ε4 allele predisposes patients to elevated ICP and perfusion disorders in white matter regions during the first 72 h after aSAH. The presence of an APOE ε4 allele plays an important role in the early brain injury response to aSAH.